2002
DOI: 10.1164/ajrccm.165.5.2104087
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-disordered Breathing and Insulin Resistance in Middle-aged and Overweight Men

Abstract: Sleep-disordered breathing is a prevalent condition associated with impairment of daytime function and may predispose individuals to metabolic abnormalities independent of obesity. The primary objective of this study was to determine the metabolic consequences and community prevalence of sleep-disordered breathing in mildly obese, but otherwise healthy, individuals. One hundred and fifty healthy men, without diabetes or cardiopulmonary disease, were recruited from the community. Measurements included polysomno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
508
8
24

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 862 publications
(565 citation statements)
references
References 44 publications
25
508
8
24
Order By: Relevance
“…However, the conclusion of this study differs from previous studies focused on increased BP, lipid profile, insulin resistance and respiratory disturbance index [2][3][4]. This inconsistence may partly be explained by the small sample size in this study, which should be estimated through power calculations (a two-sided confidence level of 99.9% and power of 80%).…”
Section: Dear Editorcontrasting
confidence: 80%
“…However, the conclusion of this study differs from previous studies focused on increased BP, lipid profile, insulin resistance and respiratory disturbance index [2][3][4]. This inconsistence may partly be explained by the small sample size in this study, which should be estimated through power calculations (a two-sided confidence level of 99.9% and power of 80%).…”
Section: Dear Editorcontrasting
confidence: 80%
“…A more recent study on insulin resistance, visceral obesity, and cytokines in obstructive sleep apnea indicated that mean plasma insulin levels were significantly higher than body mass index-matched controls, suggesting that sleep-disordered breathing is an independent risk factor for hyperinsulinemia [21]. Punjabi et al [9] also demonstrated that sleep-disordered breathing was associated with impaired glucose tolerance and insulin resistance independent of obesity in healthy men, without diabetes or cardiopulmonary disease. Our findings demonstrate that habitual snoring was not significantly associated with high fasting glucose adjusting for age, abdominal obesity, and the other components of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 98%
“…Several biochemical alterations including low HDL-cholesterol, elevated serum triglycerides, glucose intolerance, and hyperinsulinemia are independently associated with increased risk of cardiovascular diseases [9,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Although OSA patients commonly demonstrate one or more established cardiovascular risk factors, there is now a considerable body of evidence indicating that OSA itself is an independent cardiovascular risk factor. 3,[9][10][11][12][13][14][15][16] Arterial stiffness determines how quickly the pulse wave generated by the contracting heart travels to the periphery and is reflected back. The larger arteries of the cardiovascular system are critical in the conduction of blood flow to the periphery.…”
Section: Introductionmentioning
confidence: 99%